2007
DOI: 10.1016/j.nimb.2007.01.189
|View full text |Cite
|
Sign up to set email alerts
|

Progress on a gas-accepting ion source for continuous-flow accelerator mass spectrometry

Abstract: A gas-accepting microwave-plasma ion source is being developed for continuous-flow Accelerator Mass Spectrometry (AMS). Characteristics of the ion source will be presented. Schemes for connecting a gas or liquid chromatograph to the ion source will also be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…This source was modeled after a source originally built at Atomic Energy of Canada Limited, Chalk River, Ontario, Canada for H + beams and subsequently developed at NOSAMS [5,6,7] for 14 C AMS. In comparison to the prototype, the newly constructed source has several improvements including: (i) improved control of the magnetic field (by using solenoid magnets rather than permanent magnets), (ii) the ability to operate at potentials higher than 30 kV, (iii) better (i.e., close) coupling to the magnesium charge-exchange canal, (iv) the use of commerciallyavailable brazed insulators (as opposed to polyvinyl acetate glued ceramic/metal joints), (v) a reduction in internal O-ring water seals, and (vi) improved alignment capability.…”
Section: The Gas Ion Sourcementioning
confidence: 99%
“…This source was modeled after a source originally built at Atomic Energy of Canada Limited, Chalk River, Ontario, Canada for H + beams and subsequently developed at NOSAMS [5,6,7] for 14 C AMS. In comparison to the prototype, the newly constructed source has several improvements including: (i) improved control of the magnetic field (by using solenoid magnets rather than permanent magnets), (ii) the ability to operate at potentials higher than 30 kV, (iii) better (i.e., close) coupling to the magnesium charge-exchange canal, (iv) the use of commerciallyavailable brazed insulators (as opposed to polyvinyl acetate glued ceramic/metal joints), (v) a reduction in internal O-ring water seals, and (vi) improved alignment capability.…”
Section: The Gas Ion Sourcementioning
confidence: 99%
“…To date it has not been shown that negative carbon ions can be efficiently extracted from the plasma of a gas ion source. This makes it necessary to couple such an ion source to a charge exchange canal (CxC), an approach we have described elsewhere [3][4][5][6]. While the total negative ion efficiency of such an assembly is at least 1-2 orders of magnitude lower than that of a modern sputter ion source, the very large positive currents extractable from a microwave plasma allow the analyzable negative currents to be comparable to an average sputter source, if sample size is not the limiting factor.…”
Section: Introductionmentioning
confidence: 99%
“…Systems incorporating an elemental analyzer (EA) (Rottenbach et al 2008;Szidat 2009), gas chromatograph (GC) (Hughey et al 2000;Bronk Ramsey et al 2004;Flarakos et al 2008), or high-performance liquid chromatograph (HPLC) Skipper et al 2004) have been developed permitting real-time compound-specific radiocarbon analysis (CSRA). The main challenges in these cases have largely been technical.…”
Section: Introductionmentioning
confidence: 99%
“…At the National Ocean Sciences AMS facility (NOSAMS), we have developed a gas accepting ion source with an alternative design for continuous flow GC-AMS (Schneider et al 2004;Roberts et al 2007). A 2.45-GHz microwave ion source generates a plasma, which is confined in a solenoidal magnetic field.…”
Section: Introductionmentioning
confidence: 99%